Pembentukan Karakter Peserta Didik melalui Experiental Learning di SD Negeri Keraton - Faslia, Faslia; Salsafira, Salsafira; Sabaria, Sabaria; Rhamadani, Suci Suci; Putri, Agista (Universitas Pahlawan Tuanku Tambusai, 2024)
Character education must be fostered from an early age and intensified from elementary school level. This research aims to describe the implementation of the Experiential Learning learning model at Keraton State Elementary School. The approach used in this research is qualitative with research subjects consisting of educators, students and the principal of SD Negeri Keraton. Data was collected through observation, interviews and documentation. The research results show that the character education implemented in this school includes various aspects such as religiosity, love of cleanliness and the environment, honesty, caring, discipline, tolerance and respect for other people. Although there are challenges in implementing the experiential learning model, such as designing appropriate experiential activities and ensuring consistency in implementation, research results show that this model is effective in shaping student character.